ERS International Congress 2022: highlights from the Paediatrics Assembly - Ardura-Garcia, Cristina; Kainz, Katharina; Mallet, Maria Christina; Petrarca, Laura; Berlot, Jasna Rodman; Slaats, Monique; Streibel, Carmen; Vijverberg, Susanne; Williams, Emma E.; Goutaki, Myrofora; Gray, Diane M.; Lavizzari, Anna; et al. (ERJ Open Research, 2023)
This review has been prepared by the Early Career Members and Chairs of the European Respiratory Society (ERS) Assembly 7: Paediatrics. We here summarise the highlights of the advances in paediatric respiratory research presented at the ERS International Congress 2022. The eight scientific groups of this Assembly cover a wide range of research areas, including respiratory physiology and sleep, asthma and allergy, cystic fibrosis (CF), respiratory infection and immunology, neonatology and intensive care, respiratory epidemiology, bronchology, and lung and airway developmental biology. Specifically, we report on abstracts presented at the congress on the effect of high altitude on sleep, sleep disorders, the hypoxic challenge test, and measurements of ventilation inhomogeneity. We discuss prevention of preschool wheeze and asthma, and new asthma medications. In children with CF, we describe how to monitor the effect of CF transmembrane conductance regulator modulator therapy. We present respiratory manifestations and chronic lung disease associated with common variable immunodeficiency. Furthermore, we discuss how to monitor respiratory function in neonatal and paediatric intensive care units. In respiratory epidemiology, we present the latest news from population-based and clinical cohort studies. We also focus on innovative and interventional procedures for the paediatric airway, such as cryotherapy. Finally, we stress the importance of better understanding the molecular mechanisms underlying normal and abnormal lung development. - Tweetable abstract ERSpublications - click to tweetHighlights from the Paediatrics Assembly at the #ERSCongress 2022 https://bit.ly/3lm7TDq